2010
DOI: 10.1007/s12010-010-9081-2
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and Characterization of a Serine Collagenolytic Extract from Snow Crab (Chionoecetes opilio) By-products

Abstract: Sequential acidic precipitation followed by a single chromatographic step (gel filtration) allowed the recovery of a collagenolytic fraction containing several proteases from by-products of snow crab (Chionoecetes opilio). The partial purification was particularly efficient to recover tryptic (purification fold = 1,352.5; yield = 110%) but also chymotryptic, elastolytic, and collagenolytic activities. A temperature of 40 °C and pH 8.0-8.5 were optimal for enzyme activity, which was stable for 2 h under these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
(62 reference statements)
4
6
0
1
Order By: Relevance
“…MUKHERJEE et al (2009) observed that pH 5.0 improved the activity of enzymes from species of sponge (R. odorabile). The stability of pH has also been reported for aquatic species such as fish, crustaceans, and sponges, and optimal values were found oscillating between < 5.0 and > 10.0 (TURKIEWIC et al, 1991;KRISTJÁMSSON et al, 1995;TERUEL and SIMPSON, 1995;MURADO et al, 2009;WU et al, 2010a;WU et al, 2010b;HAYET et al, 2011;SOUCHET and LAPLANTE, 2011;SUPHATHARAPRATEEP et al, 2011;BAEHAKI et al, 2012).…”
Section: Temperature and Ph Assay Of The Collagenolytic Enzymementioning
confidence: 91%
See 2 more Smart Citations
“…MUKHERJEE et al (2009) observed that pH 5.0 improved the activity of enzymes from species of sponge (R. odorabile). The stability of pH has also been reported for aquatic species such as fish, crustaceans, and sponges, and optimal values were found oscillating between < 5.0 and > 10.0 (TURKIEWIC et al, 1991;KRISTJÁMSSON et al, 1995;TERUEL and SIMPSON, 1995;MURADO et al, 2009;WU et al, 2010a;WU et al, 2010b;HAYET et al, 2011;SOUCHET and LAPLANTE, 2011;SUPHATHARAPRATEEP et al, 2011;BAEHAKI et al, 2012).…”
Section: Temperature and Ph Assay Of The Collagenolytic Enzymementioning
confidence: 91%
“…TERUEL andSIMPSON (1995), BYUN et al (2002), , SOUCHET andLAPLANTE (2011) andDABOOR et al (2012) reported an optimum pH of 7.5 to enzymes obtained from the aquatic species: winter flounder (P. americanus), tuna (T. thymus), Mackerel (S. japonicus), snow crab (Chionoecetes opilio) and fish waste, respectively. KRISTJÁMSSON et al (1995), ROY et al (1996) and BAEHAKI et al (2012) found an optimum pH of 7.0 for enzymes from Atlantic cod (G. morhua), greenshore crab (C. maenas) and Bacillus licheniformis, respectively.…”
Section: Temperature and Ph Assay Of The Collagenolytic Enzymementioning
confidence: 99%
See 1 more Smart Citation
“…Souchet and Laplante [28] also detected the collagenolytic activity (13.3 IU/mg) in byproducts of snow crab Chionoecetes opilio. Currently, much of the collagenase used in the market is of microbial origin.…”
Section: Discussionmentioning
confidence: 92%
“…Para a maioria das espécies aquáticas, esse pH situa-se numa faixa entre 6,0 e 8,0 , Daboor et al, 2010. A estabilidade enzimática às variações de pH foi reportada para espécies aquáticas (peixes, crustáceos, esponjas), variando entre 5,0 a 10,0, a escala de recuperação de atividade (Kristjánsson et al, 1995, Teruel and Simpson, 1995, Lima et al, 2009, Mukherjee et al, 2009, Murado et al, 2009, Wu et al, 2010a, Hayet et al, 2011, Souchet and Laplante, 2011.…”
Section: Fatores Que Afetam a Atividade Enzimáticaunclassified